Adopting a lay navigator training programme in primary care - Toal-Sullivan, Darene; Lemonde, Manon; Gauthier, Alain P.; Dahrouge, Simone (Health Education Journal, 2021)
Introduction: There is growing interest in the role and use of patient navigators within the health care system. Currently, qualifications and training expectations documented in the literature vary tremendously depending on context and patient population. This paper details the theoretical and pedagogical principles used to develop, implement and evaluate a training programme for lay patient navigators working in a primary care setting. Methods: The planning process involved (a) conducting an educational needs assessment, (b) identifying the theory underpinning the curriculum, (c) developing learning objectives and teaching strategies, (d) formulating evaluation methods, (e) implementing the programme and (f) refining the curriculum based on evaluation feedback and lessons learned. The training programme was first implemented in May 2017 and has evolved over the past 3 years based on our observations and feedback from the programme participants. Results: The training programme involves a total of 25 hours of online and face-to-face education sessions, and ongoing community mentorship from experienced navigators. All training components are rooted in theoretical principles and proven pedagogical approaches. The knowledge, skills and abilities acquired are also tied to core competencies of the role of lay patient navigator. Conclusion: The development of this lay navigator training programme was carefully designed with evidence-based competencies and practical realities to ensure rigour in preparing and supporting navigators’ work in primary care settings.
Bien que cette étude ne porte pas spécifiquement sur les CLOSM, la formation développée inclut un contenu sur l'offre active. Although this study does not focus specifically on CLOSMs, the training programme developed includes content on offering services in French to Francophones (Active Offer).